Time to Change Your Investment Model. Issue 4 (1st October 2017) - Gu, Feng; Lev, Baruch
Abstract : We demonstrate empirically that the gains from predicting corporate earnings, or consensus hits and misses—an activity at the core of most investment methodologies—have been shrinking fast over the past 30 years. We identify the main reasons for this loss of earnings relevance and propose an improved alternative to current investment methodologies, one that focuses on the "strategic assets" of the enterprise and their contribution to maintaining the company's competitive edge. We demonstrate this investment methodology using subscription-based companies. Abstract : Disclosure: The authors report no conflicts of interest. Editor's Note Submitted 24 November 2016 Accepted 26 April 2017 by Stephen J. Brown